Hubungan Proklamasi Dengan Pancasila Dan Pembukaan Undang-Undang Dasar 1945 (Lex Jurnalica, 2006)
The events that happened after the formulation of Pancasila, Proclamation of Independence and the Preambule of UUD 1945 are very important. Contents of the Preambule of UUD 1945 ia a sacred message from the Proclamation of Independence. Construstion of the independent state of Indonesia can be seen and understood in the Preambule of UUD 1945, in which contains the ideology of the Republic of Indonesia namely Pancasila. This paper has studied the relation between The Proclamation of Independence with Pancasila and Preambule of UUD 1945.Keywords: Proclamation of Independence RI, Pancasila, Preambule of UUD 1945